Nature, wealth, and power: emerging best practice for revitalizing rural Africa - United States Agency for International Development (USAID in collaboration with CIFOR, Winrock International, WRI, IRG, 2002)
This document is about rural development in Africa. It is a preliminary statement of lessons learned from more than 20 years of natural resource-based development in rural Africa. Twenty years ago, natural resource management programs took a predominantly technical approach and followed by economic approach to getting rural development moving and responding to perceived environmental crises. The limitations of these approaches revealed as projects failed to meet their objectives and be sustainable. More recently, it has become clear that the governance aspects of rural development are also key. Experience demonstrates that programs that integrate nature, wealth, and power (good governance) have promising results. This experience generated a set of principles-summarized in this booklet as action steps-that can serve as a guide to investment in rural Africa. The three case studies presented: Namibia, Madagascar, and Mali illustrate the effectiveness of the integration of all three dimensions and the various principles and actions recommended under each dimension.